GIS application of USLE and MUSLE to estimate erosion and suspended sediment load in experimental catchments, Valdivia, Chile. - Iroumé, Andrés; Carey, Patricio; Bronstert, Axel; Huber, Anton; Palacios, Hardin (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
This paper presents the results of a research aimed to quantify suspended sediment transport in three experimental catchments in southern Chile, to compare measured suspended sediment load with estimated erosion using the Universal Soil Loss Equation (USLE) applied in a GIS environment and to validate de Modified Universal Soil Loss Equation (MUSLE) used to estimate suspended sediment loads from forest catchments. The catchments are Los Pinos (94.2 ha), Los Ulmos 1 (12.6 ha) and Los Ulmos 2 (17.7 ha). Soil losses estimated with USLE for the three catchments are higher than those measured in runoff experimental lots under bare soil conditions, which could indicate an overestimation of the LS calculated in GIS and the fact that the USLE model does not compute sediment deposit and storage within the catchment. A statistical significant relation was found between measured and estimated (MUSLE) suspended sediment load, which would indicate that this model could be applied to estimate suspended sediment load from small catchments in southern Chile.